EVALUATION OF PEER ASSISTED LEARNING IN EVIDENCE BASED MEDICINE COURSE: A PILOT STUDY AT UNIVERSITY OF GLASGOW - Habib, Syed Hamid; Malik, Muhammad Omar; Fatima, Sadia; Shah, Inayat (Journal of Ayub Medical College Abbottabad, 2017)
Background: Peer Assisted Learning (PAL) is a well-established approach in learning and is increasingly being utilized in the medical education system. It is a process where active help of peer group members is taken for learning. This study aimed to look at the impact of peer assisted learning on the students at the end of the session. Methods: Sixteen Postgraduate students attending Evidence Based Medicine (EBM) course spanning over two semesters (6 months each) were recruited. It was a cross sectional study and non-probability convenience sampling technique was used for gathering data. All students enrolled in EBM course conducted an hour-long PAL session during the coursework. At the end of the semester a link to an online questionnaire was sent to all the participants. A set of both open and closed ended questions were included in the questionnaire. Results: Response rate was 87.5%, 14 out of the 16 students completed the questionnaire. The results showed an affirmative change in the behaviour and attitude of the participants’ after the workshops. Majority of the respondents were of the opinion that it was a valuable experience and they benefitted through involvement in the process. Most of the post-graduate students suggested that it should be implemented in post graduate studies especially medical education. Conclusion: PAL is more interactive and informal way of teaching and it helps in the professional development, if peers from different specialties are gathered. However, study with a larger sample size are suggested to prove the generalizability of this assertion. Keywords: Peer Assisted Learning; Peer Learning; Evidence Based Medicine